Characterization and performance analysis of multi-stack vanadium redox flow battery - Nurizzati, Md. Nizam (2019)
Energy storage technology is a technology that manages power supply system to create energy and cost saving for utilities and consumers. Wind power, solar, and hydroelectric power are examples of renewable resources and are used as an alternative energy and energy storage for power supply. Redox Flow Battery (RFB) is an electrochemical system that could repeatedly convert and store energy in large scale. Vanadium Redox Flow Battery (VRFB) is one of the noteworthy energy storage due to the fact that it eliminates the cross contamination of electrolyte problem that occurs in other redox flow battery. Sharing the same principle of storing the energy externally as fuel cells, RFB has the advantage of being able to electrically reverse the electrochemical reaction within the cell. Much of the emphasis of recent research on vanadium redox flow battery (VRFB) has been focused under field testing, demonstration stage and the investigation of leakage problem caused by rubber seal, membrane, carbon felt and fitting in construction, but information on construction, experimental characterization, electrolyte preparation, and overall systems under study is still minimal. This project focuses on the characterization and performance analysis for linearity of a multi-stack VRFB for different cell stack sizes of 25 cm2, 56.25 cm2 and 100 cm2. The unit cell performance with respect to voltage efficiency under different performance parameters (current density, flow rates, volume of electrolytes, temperature of cell, electrode porosity and membrane conductivity) are presented along with the cell linearity findings while keeping the coulombic efficiency at its optimum value of 90%. The cell stack exhibits different characteristics under different operating parameters. The best cell design for this project is for the electrode size of 100 cm2 at current density of 50 mA/cm2, flow rate of 0.17 cm3/s, electrolyte volume of 10 cm3, cell temperature of 288.15 K, electrode porosity of 0.94 epsilon and membrane conductivity of 15 S/m. The relation between the size of electrodes in multi-stack VRFB is also analysed and discussed to develop theories for linearity in which it is found that there exists a linear relationship between different current density, flow rate, temperatures of cell and electrode porosity value with the same cell stack size but no linear relationship between different volume of electrolytes and membrane conductivity values with the same cell stack size. Ultimately, suggestion for system improvement is highlighted.